Fabrication of polyethylene terephthalate (PET) nanoparticles with fluorescent tracers for studies in mammalian cells. Issue 2 (15th December 2020) - Johnson, Leah M.; Mecham, Jeffrey B.; Krovi, Sai Archana; Moreno Caffaro, Maria M.; Aravamudhan, Shyam; Kovach, Alexander L.; Fennell, Timothy R.; Mortensen, Ninell P.
Abstract : Fluorescent nanoparticles (NPs) comprising polyethylene terephthalate (PET) with a hydrodynamic diameter of 158 ± 2 nm were synthesized in a bottom-up approach. Abstract : Fluorescent nanoparticles (NPs) comprising polyethylene terephthalate (PET) with a hydrodynamic diameter of 158 ± 2 nm were synthesized in a bottom-up approach. Concentration-dependent uptake and cytotoxicity of PET NPs in macrophages are shown. The fabrication of well-characterized NPs, derived from high-commodity polymers, will support future studies to assess effects on biological systems.